Optimization of Madura Cattle Performance Fed Ammoniated Rice Straw and Concentrate Containing Hibiscus tiliaceus Leaf - Bata, M.; Rahayu, S.; Rimbawanto, E. A.; Hartoyo, B.; Prihambodo, T. R.; Renata, M.; Umam, R. Z. (Faculty of Animal Science, IPB University, 2025)
The leaves of Hibiscus tiliaceus, known for their flavonoid and fumaric acid contents, may support more stable rumen fermentation by promoting propionic acid production and helping maintain a healthy pH in high-concentrate diets. When paired with ammoniated rice straw, this supplement could improve how cattle utilize nutrients while lowering the risk of subacute ruminal acidosis in feedlot settings. This study evaluates the effectiveness of H. tiliaceus leaf flour as a dietary supplement in feedlot Madura cattle. Fifteen cattle (initial weight 264.43 ± 22.68 kg) were assigned to three diet treatments: rice straw plus concentrate (RSC), ammoniated rice straw plus concentrate (ARSC), and ammoniated rice straw plus concentrate supplemented with HTLF (ARSC+H) and statistically analyzed using a completely randomized design. Concentrates were fed at 2.5% of body weight, while rice straw and ARS were provided ad libitum. Ammoniation involved treating rice straw with 5% urea and 2.5% cassava pulp. The treatments significantly (p<0.01) increased digestibility parameters (dry and organic matter digestibility (DMD, DMO), crude fat digestibility (CFD), crude protein digestibility (CPD), crude fiber digestibility (CFD), and nitrogen retention (NR)), microbial protein synthesis (MPS) and production (MPP), energy utilization (energy digestibility (ED), metabolizable energy output (MEO), energy retention (ER)), volatile fatty acid (VFA) production, average daily gain (ADG), and feed efficiency (FE). RSC showed lower values compared to ARSC and ARSC+H (p<0.01), while differences between ARSC and ARSC+H were not significant (p>0.05). The highest MPS, MPP, and ADG were observed in ARSC+H, with the best FE also in ARSC+H. In conclusion, ARSC+H enhances nutrient digestibility, MPS, and fattening performance in Madura cattle, indicating its potential as an effective feed strategy.